2007
DOI: 10.1152/ajpendo.00648.2006
|View full text |Cite
|
Sign up to set email alerts
|

Rhythm of the β-cell oscillator is not governed by a single regulator: multiple systems contribute to oscillatory behavior

Abstract: Heart E, Smith PJS. Rhythm of the ␤-cell oscillator is not governed by a single regulator: multiple systems contribute to oscillatory behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Our study has three main findings. First, we have shown that palmitate causes cytosolic Ca 2ϩ signals in primary human islet ␤-cells and MIN6 cells, in agreement with previous findings in other ␤-cell lines and primary mouse islets (19,22). Second, we have demonstrated that these Ca 2ϩ signals are generated by a combination of extracellular Ca 2ϩ influx and Ca 2ϩ release from intracellular stores.…”
Section: Discussionsupporting
confidence: 91%
“…Our study has three main findings. First, we have shown that palmitate causes cytosolic Ca 2ϩ signals in primary human islet ␤-cells and MIN6 cells, in agreement with previous findings in other ␤-cell lines and primary mouse islets (19,22). Second, we have demonstrated that these Ca 2ϩ signals are generated by a combination of extracellular Ca 2ϩ influx and Ca 2ϩ release from intracellular stores.…”
Section: Discussionsupporting
confidence: 91%
“…MMS induced ⌬ p and [Ca 2ϩ ] c oscillations in the rat islets indistinguishable from those produced by glucose, as well as a "classic" first-and secondphase insulin secretion, and the authors concluded that "systems other than glycolysis might control these oscillations" (213). The study was extended to methyl pyruvate and ␣-ketoisocaproate (KIC) (212). Both substrates supported regular "slow" [Ca 2ϩ ] c oscillations in single dissociated mouse islet cells.…”
Section: Is Glycolysis Needed For Slow Oscillations?mentioning
confidence: 98%
“…However, oscillations in [Ca 2+ ] i remained normal after 95-98% suppression of PFK-M activity in mouse islets (Richard et al, 2007). Moreover, oscillations of [Ca 2+ ] i are not only generated by glucose, but also by mitochondrial substrates like leucine (Grapengiesser et al, 1989b), α-ketoisocaproic acid (Martin et al, 1995;Heart and Smith, 2007) and methyl pyruvate (Heart and Smith, 2007) even in the absence of glycolytic flux (Heart and Smith, 2007), although some of these observations are controversial (Lenzen et al, 2000;Dahlgren et al, 2005). Since citrate oscillates in isolated islet mitochondria, it has also been proposed that there is an independent mitochondrial oscillator and that exported citrate may feedback-coordinate mitochondrial and glycolytic oscillations (MacDonald et al, 2003 (Detimary et al, 1998).…”
Section: Role Of Metabolism For Glucose-induced Insulin Secretionmentioning
confidence: 99%